Computer Security -- ESORICS 2009 14th European Symposium on Research in Computer Security, Saint-Malo, France, September 21-23, 2009, Proceedings - Backes, Michael; Ning, Peng (Security and Cryptology, 2009)
This book constitutes the proceedings of the 14th European Symposium on Research in Computer Security, ESORICS 2009, held in Saint-Malo, France, in September 2009. The 42 papers included in the book were carefully reviewed and selected from 220 papers. The topics covered are network security, information flow, language based security, access control, privacy, distributed systems security, security primitives, web security, cryptography, protocols, and systems security and forensics.